ChemInform Abstract: Intramolecular Cyclization of Alkylimidazoles. Issue 40 (October 2015) - Joshi, Madhur S.; Lansakara, Ashabha I.; Pigge, F. Christopher
Abstract 1, 2‐Dialkylimidazoles are converted to nucleophilic 2‐alkylidene imidazoles upon treatment with Boc2O.